STROKE PREVENTION IN INTERNIST PRACTICE - D. A. Napalkov; A. V. Zhilenko (Рациональная фармакотерапия в кардиологии)
Stroke secondary prevention in internist practice is discussed in accordance with up to date guidelines. Modern pharmacotherapy includes antiaggregants or anticoagulants, statins, and antihypertensive drugs. The choice of drugs is mostly founded on the rules of evidence based medicine, which allow adjusting individual treatment depending on clinical conditions. The composition of perindopril and indapamide is a preferred nowadays combination of antihypertensive drugs.